Proceedings of the ICAR-ACIAR Workshop on Farmyard Manure: Life Cycle Analysis and Management, February 18-20, 2003 - Acharya, C. L.; Sammi Reddy, K.; Sharma, A. K. (Indian Institute of Soil Science, 2003)
Contributed articles presented in the seminar jointly organised by ICAR and ACIAR.